Valutazione dell'efficacia delle aree marine protette nel mitigare la vulnerabilità e capacità adattativa di comunità bentoniche in scenari climatici futuri - CURIOTTO, MARTA (Pisa University, 2023)
The anthropogenic climate change is causing, globally and locally, loss of biodiversity and regression of priority habitats, making conservation and restoration of species and the ecosystem services they provide the greatest challenges of our time. According to future climate projections of temperature increases (RCPs) and socioeconomic changes (SSPs), finding environmentally and economically sustainable actions, strategies and Nature Based Solutions for climate change adaptation and mitigation is mandatory. Firstly, it is important to understand what the vulnerability and adaptive capacity of relevant species and their relative level of risk will be by the end of the century. The aim of this work is to evaluate the climate risk of some organisms of benthic communities and the mitigation effect of NBS in future climatic and socio-politic scenarios. Climate Risk Assessment is a useful tool to assess and understand the cause/effect relationship between climate change and their associated risk. It is built around the AR5/6 of IPPC guidelines, according to which the risk of a given system or species results from the combination of three dimensions: Hazard, Exposure and Vulnerability, the latter estimated as a function of its Sensitivity and Adaptive Capacity. It investigates three climate hazards (increasing temperature, marine heat waves and ocean acidification) and two human hazards (boat anchoring and nutrient loading) in order to understand the magnitude of exposure and to asses the adaptive capacity of five taxa (Posidonia oceanica, Cystoseira s.l., encrusting corallinaceae algae, Epinephelus marginatus, Paracentrotus lividus) in the presence or absence of NBS, namely the Marine Protected Areas. Then, it asseses the potential mitigation capacity of NBS to mitigate the effects of climate change. Both the Risk and the MPA Mitigation Capacity have been assessed considering two time slices (mid term and long term future) in three different socioeconomic scenarios, based on the RCPs and SSPs projections (Global ...